EFEKTIVITAS KONSELING KELOMPOK MENGGUNAAN TEKNIK ROLE PLAYING TERHADAP PENURUNAN PERILAKU BULLYING - Avrilian Hamidayana Hamidayana; Siti Nurlaila; Tri Anjar (Universitas Muhammadiyah Metro, 2026)
Abstract The purpose of this study was to determine the effectiveness of group counseling services using role-playing techniques on reducing Bullying behavior at SMP Negeri 2 Way Bungur, East Lampung Regency. This research method applies quantitative research with an experimental research type. The research stages carried out were pre-test, treatment, and post-test. The number of samples in this study was 6 people. Data collection used a questionnaire given to the research sample. Data analysis in the study used the t-test formula with the help of the Jamovi application. The results of the study showed that Bullying behavior before being given treatment was 5 students with a high category and 1 student with a medium category. Group counseling services with role-playing techniques were carried out in 3 meetings. The results of the post-test scoring of Bullying behavior after being given treatment showed a decrease in Bullying behavior with a medium and low category. Based on statistical testing using the t-test, a significant value (p) was obtained, namely 0.001 <0.05, so there is an effectiveness of group counseling services with role-playing techniques on reducing Bullying behavior.